2018
DOI: 10.1002/ase.1789
|View full text |Cite
|
Sign up to set email alerts
|

Breaking with Tradition: A Scoping Meta‐Analysis Analyzing the Effects of Student‐Centered Learning and Computer‐Aided Instruction on Student Performance in Anatomy

Abstract: While prior meta-analyses in anatomy education have explored the effects of laboratory pedagogies and histology media on learner performance, the effects of student-centered learning (SCL) and computer-aided instruction (CAI) have not been broadly evaluated. This research sought to answer the question, "How effective are student-centered pedagogies and CAI at increasing student knowledge gains in anatomy compared to traditional didactic approaches?" Relevant studies published within the past 51 years were sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 70 publications
4
54
0
3
Order By: Relevance
“…cohorts with a prior competent grasp of the relevant anatomy. This supports the findings of a recent meta-analysis of the literature showing that computer-assisted instruction was more beneficial for postgraduate and professional students (Wilson et al, 2019), where a higher level of anatomy knowledge can be expected.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…cohorts with a prior competent grasp of the relevant anatomy. This supports the findings of a recent meta-analysis of the literature showing that computer-assisted instruction was more beneficial for postgraduate and professional students (Wilson et al, 2019), where a higher level of anatomy knowledge can be expected.…”
Section: Discussionsupporting
confidence: 89%
“…For example, participants' level of learning (e.g. undergraduate, pre-clinical, or clinical), varies widely in the literature available (Wilson et al, 2019) and, as demonstrated in the current data, prior anatomical knowledge has a role to play in the effective use of high-fidelity interactive models. Furthermore, variations in the experimental paradigms used to evaluate learning, the specific taxonomy of learning, the definition of traditional resources and the time allocated for completing tasks could also be significant factors.…”
Section: Discussionmentioning
confidence: 95%
“…Examples include plastinated specimens (Riederer, 2014), clay-based models (Kooloos et al, 2014;Akle et al, 2018) and computer-based learning resources (Bryner et al, 2008;Mayfield et al, 2013;Trelease, 2016), such as digital image libraries for clinically oriented anatomy teaching (Elizondo-Omaña et al, 2005;Pujol et al, 2016) and virtual 3D models (Nicholson et al, 2006;Keedy et al, 2011;Cui et al, 2016). While computer-based 3D models act as good supplementary study aids (Wilson et al, 2019) and present a user with an interactive and dynamic 3D vision of difficult anatomical structures (Petersson et al, 2009;Pujol et al, 2016), they are limited by their image resolution, the size of the monitor and more importantly, the lack of haptic feedback (Wainman et al, 2018). Previous studies have found that students who rely only on computer models are at a significant disadvantage compared to students using traditional 3D plastinated specimens or plastic models of anatomical structures (Khot et al, 2013;Preece et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The literature is becoming increasingly populated with examples of how this type of technology is supplementing anatomy curricula, with the use of, for example, eBooks (Stirling and Birt, ; Pickering, ), smart phone and tablet applications (Lewis et al, ), social media (Hennessy et al, ; Pickering and Bickerdike, ), massive open online courses (MOOCs; Swinnerton et al, ), 3D printed specimens (McMenamin et al, ; Lim et al, ), 3D visualizations (Yammine and Violato, ), and most recently, augmented and virtual reality (Moro et al, ), all being documented. This emphasis on augmenting the traditional anatomy curricula with TEL resources has recently been supported by a meta‐analysis of blended learning courses across health care education, which highlights the positive impact such courses can have on student outcomes (Liu et al, ; Wilson et al, ).…”
Section: Introductionmentioning
confidence: 99%